AI, Merusak Pendidikan di Indonesia atau Menyadarkan Esensi Pendidikan di Indonesia? - Ivanka Harits Darwisy; Nadia Diana (Jounal Nyanadassana, 2023)
Education is considered a moral act undertaken by humans to develop individual talents and abilities, enabling proper participation in human and societal progress. Technological advances, especially in learning theory, have had a significant impact on the world of education. Technology, such as ChatGPT, has provided innovation in expanding learning resources. Even though it provides convenience, using ChatGPT in education requires wisdom and an understanding of moral values. Several educational institutions have implemented regulations regarding the use of ChatGPT, with sanctions for violators of academic ethics. This research aims to respond to the impact of ChatGPT in the learning environment to maintain the essence of education. The conclusion emphasizes the importance of the essence of education in shaping children's learning motivation, highlighting the need for an appropriate learning environment through a Holistic Education approach and contextual learning.